Archaeological heritage conservation and management - Egloff, Brian, (Access archaeology., 2019)
Archaeological heritage conservation is all too often highly conflicted. Economic interests are often at the forefront of management decision-making with heritage values given lesser, if any, consideration, but when heritage places are managed with international principles in mind the sites stand out as evidencing superior outcomes.